Corporate Time Management Tools in Managing Organizational Development in the Private and Public Sectors in the Age of Digitalization - Samoilenko Larysa Ya. (Bìznes Inform, 2025)
The article addresses theoretical issues related to corporate time management in managing organizational development in the private and public sectors. The article discusses the problem of optimizing time and achieving success in the world of digital technologies. The authors explore the impact of digital technologies on time management efficiency and propose their own definitions of time management adapted to modern realities. The article details the advantages of implementing corporate time management in enterprises, namely: completing work on time; increasing productivity; reducing stress levels; improving work quality; and achieving a balance between work and personal life. Corporate time management helps to optimize working hours, set goals, and manage processes. The authors describe the principles of building a corporate time management system that will help optimize the process of achieving specified goals and distributing time most effectively. The article also details modern tools for corporate time management, namely: task management programs; calendar applications; email management programs; note-taking applications and information organization tools that allow for storing and organizing information. The authors note that in the modern world, time management is becoming an integral part of contemporary business processes, as proper time management becomes a key factor in achieving the success of an enterprise. Digital assistants simplify and optimize the resolution of many business issues, freeing up user time to solve more significant tasks, processing large data sets, assisting in prioritization, algorithmizing tasks, optimizing business processes, and ultimately allowing individuals to manage their time most effectively and achieve success. The results of the study on modern corporate time management tools can be used both by professionals facing time management challenges in today’s digital world and by researchers working in the field of time management and enterprise efficiency.